Phenotypic screening in influenza-infected zebrafish identifies Nrf2-mediated compound protective against ischemia-reperfusion injury - Elyse Latreille; Avinash Naraiah Mukkala; Rajiv Sanwal; Junghwa Yun; Kuiru Wei; Raluca Petrut; Nikki Zamani Farahani; Tristan Philip; Leo Xu; Tom Bateman; Chuxi Pan; David E. Williams; et al. (iScience)
Summary: Excessive inflammation contributes to tissue injury in conditions including acute respiratory distress syndrome and ischemia-reperfusion. Moderation of inflammation is a potential therapeutic approach. A phenotypic screen of chemical libraries in influenza A-infected zebrafish identified aeroplysinin-1 (Ap) as a compound capable of reducing edema and improving survival. In murine models of lung injury, Ap improved oxygen saturation. Ap also reduced liver injury in a murine model of liver ischemia/reperfusion. RNA sequencing (RNA-seq) and western blotting indicated that Ap acts via the Nrf2 antioxidant pathway and knockdown of Keap1 or Nrf2 attenuated Ap’s effects. Ap was unable to improve oxygen saturation and had no effect on leukocytes in Nrf2-knockout mice. We generated a derivative of Ap that exhibited improved in vitro potency and onset of action; this compound may be useful for the treatment of inflammation. Together, our work demonstrates the value of phenotypic screening in zebrafish and describes an anti-inflammatory compound.